Processes, potential, and duration of vegetation restoration under different modes in the eastern margin ecotone of Qinghai-Tibet Plateau - Fengkui Ma (Elsevier, 2021)
This study analyzed the process of vegetation restoration in the eastern margin ecotone of Qinghai-Tibet Plateau (EMEQTP) from 2001 to 2019 under different restoration modes based on the vegetation net primary productivity (NPP) which was estimated by the Carnegie-Ames-Stanford approach (CASA) model. Then the potential NPP was calculated and the durations of NPP restoration were predicted based on the Autoregressive Integrated Moving Average (ARIMA) model. Finally, the relative importance of main parameters in the CASA model as well as global sensitivity and uncertainty were discussed. The results showed that the NPP under a natural restoration mode had the highest increase with 20.1%, and its spatial change showed an overall trend of restoration. The NPP under the comprehensive restoration mode achieved an increase of 11.5%, with the southwestern area experiencing an insignificant trend of degradation, whereas the northeastern area experiencing a significant restoration trend. As for the NPP under the artificial restoration mode, it experienced the lowest increase with 10.5%, and the northern part experiencing a significant restoration trend, whereas the southeastern part experiencing an insignificant degradation trend. In addition, the highest potential NPP of vegetation restoration would be appeared in the area under a comprehensive restoration mode. The area under an artificial restoration mode would have the lowest potential NPP of vegetation restoration, but the duration of restoration would be longest under this mode, reaching up to 64 years. Although the natural restoration mode achieved the best effect of vegetation restoration, considering the limited scope of the promotion of this mode, further attention should be placed on restoration measures and the effects of the artificial and comprehensive restoration modes. Finally, APAR, GST and PET were relatively important for the CASA model, and the parameters including Topt, GST, and PET were sensitive. Those results can offer scientific references for the management of ecological environment in the EMEQTP.